2014
DOI: 10.1053/j.seminoncol.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Steroid Hormones in Lung Cancer

Abstract: It is becoming increasingly clear that steroid hormones are involved in the biology of many organs outside the reproductive system. Evidence has been accumulating since the mid-1990’s that the lung contains receptors for both estrogen and progesterone and that these hormones have some role in lung development, pulmonary inflammation, and lung cancer. The estrogen receptor β (ERβ) is the major ER expressed in lung tissues, while inflammatory cells capable of infiltrating the lung are reported to express both ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 77 publications
1
79
0
1
Order By: Relevance
“…The presence of receptors for both estrogen (ER α, ER β and GPER) and progesterone in lung cells 29, 30 , the pulmonary physiologic abnormalities associated with the targeted inactivation of ER β receptors in female mice 31 , the ER β receptor most often expressed in human non-small cell lung cancer cell lines and in normal pulmonary tissue of sick patients 30 , illustrate the plausibility of the role of steroid hormones in lung carcinogenesis. Furthermore, some studies have indicated differences in the expression of ERs depending on the sex of the subject and the cancer histology 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of receptors for both estrogen (ER α, ER β and GPER) and progesterone in lung cells 29, 30 , the pulmonary physiologic abnormalities associated with the targeted inactivation of ER β receptors in female mice 31 , the ER β receptor most often expressed in human non-small cell lung cancer cell lines and in normal pulmonary tissue of sick patients 30 , illustrate the plausibility of the role of steroid hormones in lung carcinogenesis. Furthermore, some studies have indicated differences in the expression of ERs depending on the sex of the subject and the cancer histology 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on estrogen receptors (ER α and ER β), but some evidence exists also for progesterone and androgen receptors. Local metabolism of sex steroids may also be important, as suggested by the presence of sex steroids synthesising enzymes in lung parenchyma 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Results of studies from ER␣-negative/progesterone receptor-negative (ER␣ -/PR -) MDA-MB-453 and MDA-MB-468 breast cancer cell lines found that ER␤ can increase proliferation and survival suggesting that estrogen dependent activation of ER␤ in the absence of overriding effects of ER␣ may promote tumor growth (45). Although there are relatively few studies examining the role of ER␤ in tumors like Med that typically lack ER␣, lung cancer stands as an example of another nonreproductive estrogen responsive cancer that expresses ER␤ and not ER␣ (63). Similar to Med, in human lung cancers, ER␤ and IGF1R expression levels are positively correlated, and increased levels of their expression are associated with poor prognosis (64).…”
Section: Discussionmentioning
confidence: 99%
“…There is concerted interest in the role ofhormone therapy influence on steroid receptor function in mediating the development and progression of many common cancers including those of the breast, endometrium, ovary, colon and rectum, and lung (1, 2, 3, 4). Relevant findings on this issue, with emphasis on randomized clinical trial findings, follows.…”
mentioning
confidence: 99%